Integrated supply chain management and fourth party logistics - Gökkaya, Can Gökçen (My University, 2001)
ENTEGRE EDİLMİŞ TEDARİK ZİNCİRİ YÖNETİMİ VE DÖRDÜNCÜ PARTİ LOJİSTİK Üçüncü parti lojistik firmaları kendilerinden beklenen getirileri sağlayamadığı için dünya yeni bir lojistik çözümü aramaya başladı. Dördüncü parti bu yeni çözüme verilen isimdir. Dördüncü parti lojistik firması, detaylı kaynak zincirleri çözümü sağlamak için, kendi kaynaklarını, yeteneklerini ve teknolojisini çeşitli hizmet sağlayıcılarla birleştirip yöneten bir kaynak zincirleri entegratörüdür. Türkiye'de dördüncü parti lojistik hizmeti sağlayan bir firma olmadığından araştırmacı uygulamasını Türkiye'de bu konunun ilk uygulayıcısı olmak isteyen bir şirkette yapmıştır. Araştırma kısmında lojistik marketler, prosesler, depo maliyet karşılaştırmaları, ve organizasyon yapısı detaylı olarak incelenmiştir. Data toplarken ikincil datalardan yaralanıldığı gibi gözlem ve röportajlarda yapılmıştır. 21 nci yüzyılın bilgi teknolojisinin bu konudaki faydaları da gözardı edilemez. İntranet, internet ve çeşitli software teknolojileri lojistik hizmet sağlatıcılara üçüncü partilikten dördüncü partiliğe geçiş şansı vermiştir.

World has begun to investigate a new logistics solution, despite third party logistics providers couldn't give the expected benefits from them and couldn't satisfy firms total logistics requirements. Fourth party logistics is the name which is given to this new solution. The fourth party logistics provider is a supply chain integrator that assembles and manages the resources, capabilities, and technology of its own organization with those of complementary service providers to deliver a comprehensive supply chain solution. It is analyzed in the literature survey that the supply chain management, outsourcing and fourth party logistics. Due to lack of any fourth party logistics provider in Turkey, researcher preferred to make implementation in a logistics company that wants to be first applier of fourth party logistics provider in Turkey. The logistics markets, the warehouse comparisons, the processes, the organization structure and the IT structure were examined and designed for the logistics company in depth. Secondary data, observations and especially depth interviews were used for data collection. We can't ignore the IT technology of 21th century. With the help of intranet, extranet and internet logistics providers could find a chance to change from third parties to fourth parties.
Keywords: Genel yönetim; KAYNAK; Lojistik; Şirketler; Üretim yönetimi